The value of p3-q3, if p-q=5/7 and pq=7/3?
Answers
Answered by
2
(p-q)3=p3-q3+3pq (p-q)
p3-q3=(p-q)3-3pq (p-q)
=(5/7)3-3 (7/3)(5/7)
=(125/343)-5
=(125/343)-1715/343
=(-1590/343)
Therefore, p3-q3=(-1590/343)
p3-q3=(p-q)3-3pq (p-q)
=(5/7)3-3 (7/3)(5/7)
=(125/343)-5
=(125/343)-1715/343
=(-1590/343)
Therefore, p3-q3=(-1590/343)
Answered by
0
Answer:
Step-by-step explanation:
(p-q)3=p3-q3+3pq (p-q)
p3-q3=(p-q)3-3pq (p-q)
=(5/7)3-3 (7/3)(5/7)
=(125/343)-5
=(125/343)-1715/343
=(-1590/343)
Therefore, p3-q3=(-1590/343)
Similar questions